Analysis of the effect of return on assets and return on equity on stock prices pt. (Persero) Mandiri bank TBK - Sulaiman, Sulaiman (International Journal of Accounting and Economics Studies, 2024)
The capital market is a means of corporate finance through which companies obtain capital from investors. The main objective of investors who buy shares is to obtain dividends from the difference between the sale price and the purchase price of the shares. The share price is the price per share of the company issued on the stock exchange. This study aims to examine the relationship between return on assets and return on equity at PT. (PERSERO) MANDIRI Tbk. During the period 2019-2021. The purpose of this research is to discover and analyze the effect of return on assets and return on equity on stock prices at PT. (PERSERO) Mandiri BankTbk. The research method used is descriptive and quantitative methods. The analytical tool used is multiple linear regression and the coefficient of determination. Based on the results of the study, there is no effect (H0 is accepted) of return on assets (ROA) and return on equity (ROE) on stock prices.